Influence Of Relationship and Quality of Service on Customer Trust and The Impact On Customer Loyalty - Udin Ahidin; Icih Tarsih; Surya Budiman; Kasmad Kasmad (STMIK Dharma Wacana, 2022)
The purpose of this study was to study the empirical relationship to trust, service quality to trust, relationship and service quality to trust, and trust in loyalty, both partially and simultaneously at PT BPR Makmur Artha Sedaya Pamulang, South Tangerang City. Quantitative associative research methods with verification research. PT BPR Makmur Artha Sedaya Pamulang Kota Tangerang Selatan. A total of 1153 income. The number of research samples is 92 respondents. Method of collecting data; observation, documentation, and questionnaire. Data analysis method; Analysis of the feasibility test of the data, namely Validity Test, Reliability Test, and Classical Assumption Test. Data analysis using inferencing statistics: Simple Linear Regression Test, Multiple Linear Regression Test, Determination Coefficient Test, Hypothesis Test (t-Test and Test f). The results showed that there was a positive and significant relationship between the relationship to trust, related positively and significantly to the partial quality of trust, positively and significantly related simultaneously between the relationship and service quality to trust, positively and significantly related to the trust priority to sales loyalty at PT. BPR Makmur Artha Sedaya Pamulang City of South Tangerang